PENGARUH TOTAL QUALITY MANAGEMENT (TQM) TERHADAP KINERJA OPERASIONAL PADA PERUSAHAAN JASA PINDAHAN - Pangestika, Pramesti; Sembiring, Rosali (Bussman Journal : Indonesian Journal of Business and Management, 2025)
This study aims to analyze the influence of Total Quality Management (TQM) on operational performance in the moving services company Media Mover. The TQM elements examined in this research include customer focus, quality obsession, continuous system improvement, and employee involvement and empowerment. This study employs a quantitative approach using the SEM-PLS method through the SmartPLS 4.0 application. The sampling technique used is total sampling, with a total of 27 participants involving all employees of XYZ company. The results of the study indicate that: (1) Customer focus has no significant effect on operational performance; (2) Continuous system improvement has no significant effect on operational performance; (3) Employee involvement and empowerment have a significant effect on operational performance. The TQM approach can provide valuable insights for improving the company. In this context, it helps identify problem areas and anticipate further losses. Thus, the company can focus on its core competitiveness and continuously enhance its operational performance